THE EFFECT OF DISCOVERY LEARNING LEARNING MODELS ON STUDENT PHYSICS LEARNING OUTCOMES CLASS X SMA - Sesarius Walo; Ilyas Ilyas; Ana Silfiani Rahmawati (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
This study aims to determine the effect of discovery learning learning models on the physics learning outcomes of class X SMA Karya Nangapanda in the 2019/2020 academic year. This type of research is quantitative research. The research sample was students of class X MIA, amounting to 16 people. Data collection techniques used are documentation techniques supported by interview techniques. Documentation data is the result of a test test physics class X MIA on KD 3.2 (the essence of physics) and KD 3.3 (measurement) for the 2019/2020 school year. The results showed that the dicovery learning model had no effect on the physics learning outcomes of class X SMA Karya Nangapanda for the 2019/2020 academic year. Ha line is shown by the results of data analysis with a significant level of 0.05 and a confidence level of 95% so that the sig value is obtained. 0,105 > 0,05.